(untitled) (Swiss Medical Weekly, 2021)
Digital proximity tracing has been promoted as a major technological innovation for its potential added benefits of greater speed, wider reach and better scalability compared with traditional manual contact tracing. First launched in Switzerland on 25 June 2020, the SwissCovid digital proximity tracing app has now been in use for more than one year. In light of this milestone, we raise the questions: What is currently known about the role of SwissCovid in mitigating the pandemic? Were the expectations fulfilled? In this review, we will summarise the current state of the literature from empirical studies on the adoption, performance and effectiveness of SwissCovid. The review consists of three sections. The first section summarizes findings from effectiveness studies, which suggest that SwissCovid exposure notifications contributed to preventive actions in 76% of exposure notification recipients and were associated with a faster quarantine time in some SwissCovid user groups. The second describes the public perception and current state of adoption of SwissCovid in Switzerland in light of prevalent misconceptions and overemphasised expectations. the third places the evidence on SwissCovid in an international context. Specifically, we compare key performance indicators of SwissCovid, which are of similar magnitude as for digital proximity tracing apps from other European countries. Using findings from Switzerland, we subsequently derive a preliminary measure of the population-level effectiveness of digital proximity tracing apps. We estimate that exposure notifications may have contributed to the notification and identification of 500 to 1000 SARS-CoV-2-positive app users per month. We explore why this effectiveness estimation is somewhat lower when compared with Germany or the United Kingdom. In light of the presented evidence, we conclude that digital proximity tracing works well in specific contexts, such as in mitigating non-household spread. However, future applications of digital proximity tracing should invest into stakeholder onboarding and increased process automatization – without deviating from the principles of voluntariness and user privacy.